A comparative study on the neurotoxicity of n-pentane, n-hexane, and n-heptane in the rat. Issue 3 (August 1980) - Takeuchi, Y; Ono, Y; Hisanaga, N; Kitoh, J; Sugiura, Y
Abstract : The neurotoxicity of n-pentane, n-hexane, and n-heptane have been studied in Wistar strain male rats after exposure to 3000 ppm of n-pentane, n-hexane, or n-heptane for 12 hours a day for 16 weeks. The nerve conduction velocity and the distal latency were measured before the beginning of the exposure and after exposure for four, eight, 12, and 16 weeks. The experiment showed that n-hexane disturbed the conduction velocity of the motor nerve and the mixed nerve and prolonged the distal latency in the rat's tail, but that n-pentane and n-heptane did not. The light and electron microscopic examination showed that the peripheral nerve, the neuromuscular junction, and the muscle fibre of the rats exposed to n-hexane were severely impaired, but those of the rats exposed to n-pentane or n-heptane showed no particular changes even after 16 weeks of exposure. These results show that n-hexane is far more toxic to the peripheral nerve of the rat than n-pentane or n-heptane. It is necessary to study the neurotoxicity of other petroleum hydrocarbons, since some reports suggest that petroleum solvents might possibly contain neurotoxic hydrocarbons other than n-hexane.